Influence of the synthesis temperature of the SnO2 layer on the optical transmitance of the glass-SnO2-CdS system (SCIÉNDO INGENIUM, 2021)
The influence of the synthesis temperature on the optical transmittance of the glass / SnO2 / CdS structure was evaluated, for which samples of thin films of SnO2 on glass were prepared, by the Spray Pyrolysis method at temperatures (340 ° C, 360 ° C, 380 ° C and 400 ° C) ± 10 ° C; then these served as substrate for the deposition of CdS films by the method deposited by chemical bath at (75 ± 2) ° C. The diffractograms for the SnO2 films showed a tetragonal crystalline structure showing that the best crystalline structure is the film whose synthesis temperature was 380 ° C. The CdS film showed a cubic structure. Within the considered synthesis temperature range, it turned out that the optical transmittance of the SnO2 films varied between 85 and 90%. Likewise, by means of atomic outside microscopy (AFM), the square average surface roughness (Rq) was evaluated as a function of the synthesis temperature, which resulted between approximately 9 to 20 nm. for the glass-SnO2-CdS system, the highest optical transmittance ranged from 50 to 70%, in the film synthesized at 380 ° C.
Keywords: Tin oxide; cadmium sulfide; thin films; Bath Chemical; Temperature Synthesis